ACTIVITY DETERMINANTS IN POSYANDU ELDERLY ACTIVITIES ON THE QUALITY OF ELDERLY LIFE IN SUDIANG COMMUNITY HEALTH CENTRE MAKASSAR - Gita Andiani Sumardi,; Arifin Seweng ,; Ridwan Amiruddin , (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
The realization of healthy, independent, quality, and productive elderly must be done with health development as early as possible during the life cycle to an advanced stage by taking into account the factors that must be avoided and protective factors that can be done to improve the health of the elderly. Elderly integrated service post (Posyandu Elderly) focuses on health services on promotive and preventive efforts needed by the elderly with the aim to improve quality of life through improving health and well-being. This study aims to analyze the determinants of posyandu activity on the quality of life of the elderly. This research was conducted in the Sudiang Health Center in Makassar City. The research design used was quantitative research with cross sectional design. The sample of this study was screened by 403 elderly people selected using cluster random sampling technique. To see the determinants of activeness of the elderly posyandu using the chi square test. The results showed that there was an effect of distance, history of disease, health perception, perceived benefits, family support and health worker support (p <0.05) on the activeness of the elderly posyandu, while there was no effect of education (p = 0.737) on the activeness of the elderly posyandu. After further test analysis with multiple logistic regression, it is known that the variables that most contribute to the activeness of the elderly in posyandu are the staff support (p = 0,000; OR (95% CI) = 33,572 (13,683 - 82,375). Mann Whitney test results showed there was an influence of the activeness of the elderly posyandu (p = 0.02) on the quality of life of the elderly. Based on the results of the study, it was concluded that the health worker support was the most influential factor in the activeness of the elderly in the Posyandu.